Cryptic degassing and protracted greenhouse climates after flood basalt events - Black, BA; Karlstrom, L; Mills, BJW; Mather, TA; Rudolph, ML; Longman, J; Merdith, A (Nature, 2024)
Large Igneous Provinces erupt highly reactive, predominantly basaltic lavas onto Earth’s surface, which should boost the weathering flux leading to long-term CO2 drawdown and cooling following cessation of volcanism. However, throughout Earth’s geological history, the aftermaths of multiple Phanerozoic Large Igneous Provinces are marked by unexpectedly protracted climatic warming and delayed biotic recovery lasting millions of years beyond the most voluminous phases of extrusive volcanism. Here we conduct geodynamic modeling of mantle melting and thermomechanical modeling of magma transport to show that rheologic feedbacks in the crust can throttle eruption rates despite continued melt generation and CO2 supply. Our results demonstrate how the mantle-derived flux of CO2 to the atmosphere during Large Igneous Provinces can decouple from rates of surface volcanism, representing an important flux driving long-term climate. Climate biogeochemical modeling spanning intervals with temporally calibrated paleoclimate data further shows how accounting for this non-eruptive cryptic CO2 can help reconcile the life cycle of Large Igneous Provinces with climate disruption and recovery during the Permian– Triassic, Mid-Miocene, and other critical moments in Earth’s climate history. These findings underscore the key role that outgassing from intrusive magmas plays in modulating our planet’s surface environment.